A new invasive weed-feeding species of Polypedilum (Pentapedilum) Kieffer from South Africa (Diptera: Chironomidae, Chironominae) - Andersen, Trond; González, Orestes C. Bello; Baars, Jan-Robert; Earle, William (Zootaxa, 2015)
Polypedilum (Pentapedilum) tuburcinatum Andersen et Bello González sp. n. is described and figured as male, female, pupa and larva based on material collected in the Eastern Cape Province in South Africa, imported into quarantine in Ireland and reared in the laboratory. The species feeds on the aquatic weed Lagarosiphon major (Ridl.) Moss ex Wager and is regarded as a promising candidate agent for biological control of this invasive weed.